Use of Hibiscus sabdariffa Calyxes in Meat Products - Santos, Eva María; Sánchez-Ortega, Irais; Lorenzo, Jose M.; Domínguez, Rubén; Munekata, Paulo E. S.; Falfán-Cortés, Reyna Nallely; Ibarra, Israel S.; Rangel-Vargas, Esmeralda (Frontiers in Animal Science, 2022)
In the search for new ingredients that counteract some of the problems associated with the consumption of meat and meat products like high contents of saturated fat, salt, cholesterol, the absence of dietary fiber, and the presence of synthetic additives, Hibiscus sabdariffa calyxes have shown good colorant, antimicrobial, and antioxidant properties. This research paper studies the use of H. sabdariffa roselle calyxes directly or by means of extracts in meat and meat products. Although its application is incipient, the results are promising. The vibrant red color of the calyxes makes calyxes suitable for their use in meat products even though the concentration must be optimized since the acid taste can detract from the overall acceptance. The antimicrobial properties contribute to safer meat products, and antioxidant effects, helping to extend the shelf life of meat products and reducing oxidative processes. Nonetheless, achieving the desired effects is still challenging since several factors can affect these functional properties.